Study of the Implications of Professional Ethics in the Application of the Latest Laws in Medical Practice - Eka Priyanto; Hj. Yeti Kurniati; Hj. Hernawati RAS (Formosa Journal of Social Sciences (FJSS), 2023)
This research investigates the impact of the implementation of recent laws related to medical practice on doctors' views and actions in facing ethical dilemmas. Through a combined approach of literature study and case analysis, we evaluate how new legal regulations influence professional ethical principles in medical decision making. The results show that changes in legal regulations give rise to ethical conflicts in medical practice, requiring a delicate balance between compliance with the law and maintaining moral integrity in healthcare services to patients